Knowledge networks as an innovation strategy in the food industrial: A case study at Danilla Foods - Jorge, Carlos Francisco Bitencourt; Valentim, Marta Lígia Pomim [UNESP]; Sutton, Michael J.D. (Universidade Federal da Paraíba, 2020)
Identify whether knowledge networks can provide a better use of information and knowledge as organizational resources. Thus, organizations must consider the process of mapping sources and informational flows in the construction of new knowledge, and consequently, build their knowledge networks in a structured way. In this sense, industries are immersed in large volumes of information and knowledge, however, they do not have a culture of valuing these resources. Thus, it is important to consider the subjects that make up these organizations, as well as their relationships in the processes that involve knowledge and information. The research universe was Danilla Foods, an industry that has as its essence the construction of new products through innovations, since an outsourced company carries out its manufacture. For this, the ‘case study’ method was used, and with this, a structured script for direct observation, closed questionnaires and structured interviews was applied throughout the organization. With the data collected, it was possible to carry out an analysis and understand how the organizational subjects access information and knowledge in the internal and external environment. In this way, it was possible to build the organization’s knowledge network, identifying specific aspects for innovation as a process. It was identified that the network is centralized in a few individuals, which can compromise the construction of new knowledge. At the end, parameters were presented in order to provide a better use of the industry in favor of its innovations through the construction of new knowledge.
Redes de conhecimento como estratégia de inovação na industrial alimentícia: Um estudo de caso na Danilla Foods
Keywords: Industry; Information. Innovation; Knowledge; Knowledge Networks